Mesenchymal Stem Cells in Tissue Repair - DiMarino, Amy M.; Caplan, Arnold I.; Bonfield, Tracey L. (Frontiers in Immunology, 2013)
The advent of mesenchymal stem cell (MSC) based therapies for clinical therapeutics has been an exciting and new innovation for the treatment of a variety of diseases associated with inflammation, tissue damage and subsequent regeneration and repair. Application-based ability to measure MSC potency and fate of the cells post-MSC therapy are the variables that confound the use of MSCs therapeutics in human diseases. An evaluation of MSC function and applications with attention to detail in the preparation as well as quality control (QC) and quality assurance (QA) are only as good as the assays that are developed. In vivo measures of efficacy and potency require an appreciation of the overall pathophysiology of the model and standardization of outcome measures. The new concepts of how MSC’s participate in the tissue regeneration and wound repair process and further, how this is impacted by estimates of efficacy and potency Are important new topics. In this regard,,, this chapter will review some of the in vitro and in vivo assays for MSC function and activity and their application to the clinical arena.